Experimental evaluation of the performance of new Copenhagen solar cooker configurations as a function of solar altitude angle - Apaolaza-Pagoaga, Xabier; Carrillo-Andrés, Antonio; Jiménez-Navarro, Juan Pablo; Rodrigues Ruivo, Celestino (Elsevier, 2024)
The Copenhagen cooker is a panel-type solar cooker that uses four flexible reflective panels to redirect solar radiation to a cooking vessel. Its concept design allows adjustment of the four panels to create new geometries that can adapt to the solar altitude angle. Originally, three geometrical configurations were presented by its creators. In this work, building upon these originals, new configurations are proposed to improve performances. To quantify performance improvement, experimental tests are performed. First, stagnation tests are carried out to identify the best configuration for different solar altitude angles. Then, the most promising new configurations and the original ones are tested, side-by-side, heating a water load and for different ranges of altitude angle: low (35 ), medium (66 ◦ ) and high (75 ◦ ). Results show that performance significantly improves. Results across the entire solar altitude angle range help general users to set the most effective configuration based on their specific conditions. Last, our experimental study suggests that tests without load can be a good predictor of the behaviour of solar cookers with load. This qualitative conclusion would allow solar cookers to be tested in shorter periods for all ranges of solar altitude angle, which is of great value for general users.
Keywords: Energía solar; Solar cooking; Copenhagen cooker; Experimental test; Test without load; Water load test